Cultural Policy for Arts Education : African-European Practises and Perspectives. - Schneider, Wolfgang. (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2022)
Arts Education as a system between aesthetic learning, cultural participation and creative experiences had been in focus of research ateliers in South Africa, Tanzania, Lebanon and Germany as part of the Hildesheim UNESCO Chair between 2012 to 2020 to discuss Cultural Policy for Arts Education between the Global South and the Global North.